Revisiting (16) Psyche: implications of the new shape model for its surface and surroundings - Martin, A. [UNESP]; Winter, O. C. [UNESP]; Sfair, R. [UNESP]; Amarante, A. [UNESP] (Springer Nature, 2025)
The asteroid Psyche is classified as an M-type asteroid. Initially, its density was considered high, reaching values of up to 7.6 g/cm3$$\hbox {cm}^3$$, which suggested an almost entirely metallic composition. However, more recent studies propose a lower density, ranging between 3.4 g/cm3$$\hbox {cm}^3$$ and 4.1 g/cm3$$\hbox {cm}^3$$, indicating the possibility of a mixture of metal and silicates. In this study, we investigate surface characteristics and the dynamics around the asteroid Psyche using computational tools, the recently estimated range of densities, and the latest shape model presented by [Shepard et al. Planetary Sci. J. 2(4):125, 2021]. We analyzed the effects of the geopotential and solar radiation pressure on particles orbiting the asteroid and how these factors may influence the trajectory of the Psyche spacecraft. When comparing the latest shape model with the one from [Shepard et al. Icarus 281:388–403, 2017], the differences observed in tilt and slope angles reflect changes in shape, density, and model resolution. We identified four equilibrium points around the asteroid, all of which are unstable, indicating the absence of nearby regions, where particles could remain confined, a condition potentially favorable for the Psyche spacecraft, as it reduces the presence of debris along its orbital path. Numerical simulations considering only the action of the geopotential revealed that approximately 50% of a set of particles initially distributed up to 450 km from Psyche survive. Under the influence of solar radiation pressure, a similar survival rate is observed for particles with radii between 102$$10^2$$ and 104μ$$10^4 \mu$$m. However, particles with a radius of 10μ$$10 \mu$$m showed a survival rate of approximately 1%$$\%$$. These results suggest that larger particles may pose a risk to the mission, especially during the transition to orbit D. The results also show that the Psyche spacecraft has a mass-to-area ratio equivalent to that of a particle with a radius on the order of 103μ$$10^3 \mu$$m, making it susceptible to the effects of radiation pressure. In the absence of any external force, the spacecraft could collide with the asteroid in up to 30 days.